Rethinking Traditional Institutionals Participation in Coral Reef Resource Management - Indar, Yusran Nur; Buhari, Nurliah (Journal of Indonesian Coral Reefs, 2011)
Historical review indicated traditional institution has vital role in determining the success or the failure of community-based coastal resources management in many countries. Dynamic or different perceptions over the implementation of their traditional institution in this case might derived from communities dynamic over livelihood strategy, dependency upon the resources, perception over the resources and complexity of community and government institutional relations. Therefore, it is suggested that information on traditional institution implementation and understanding dynamics should become foundation in any nationally coral reefs rehabilitation and management initiation where local coastal communities are expected to success the program. This paper will focus on various aspects of traditional institution participation and its dynamic implementation in coral reef resources management that nationally initiated by COREMAP in South Sulawesi, Indonesia.